Journal of international economics. (Amsterdam Elsevier, 1995)
​The Journal of International Economics is intended to serve as the primary outlet for theoretical and empirical research in all areas of international economics. These include, but are not limited to the following: trade patterns, commercial policy; international institutions; exchange rates; open economy macroeconomics; international finance; international factor mobility.
Published quarterly 2/3 vol. per year
Keywords: International Trade; INTERNATIONAL ECONOMIC RELATIONS; INTERNATIONAL TRADE; INTERNATIONAL ECONOMY; ECONOMIC RESEARCH; PERIODICALS